Paciente femenina de 25 años de edad con enfermedad celíaca - Yépez Murillo, Diana Michelle (2019)
It is the clinical case of a patient female 25 years old, a native of the city of Babahoyo, married to medical diagnosis of celiac disease by intestinal biopsy. Celiac disease (EC) , is an autoimmune disease that mainly affects the mucosa of the small intestine which trigger is the ingestion of gluten, gluten is a set of proteins which are cereals we have for example wheat, barley and rye, in diagnosing celiac disease is the result of the interaction of gluten with genetic, environmental and immunological factors, which sets according to the clinical history, serological and endoscopic biopsy of duodenum and that for their treatment is necessary to make a gluten-free diet. This clinical case aims to evaluate the nutritional status and carry out a plan of power based on the needs of the patient, proceed with the informed consent of the treatment, is the nutritional assessment, dietary prescription, also provides the respective nutritional counseling, and is concluded determining the nutritional status of the patient, also achieved demonstrate its integral nutritional diagnosis with the following indicators: assessment anthropometric, biochemical, clinical / physics and dietetics, manages to intervene with a meal plan according to the nutritional needs of the patient with an example of menu, the respective nutritional recommendations and each control managed demonstrate positive results in its nutritional follow-up with the previously mentioned indicators compliance with the objectives set.